Development of Human Rights in European and Ukrainian Constitutional Acts from the 18th to the 20th Centuries - Khudoiar, Lesia; Kozynets, Olena; Nitchenko, Аlla; Liubych, Oleksandr; Romanenko, Liudmyla (Jurnal Cita Hukum, 2025)
Human rights in constitutional acts are essential to building the legal framework of Europe and Ukraine. The topic is considered relevant since it is necessary to analyse the influence of historical, political, and social processes on creating contemporary legal norms to protect human rights. Therefore, the study aims to assess the evolution of human rights in Europe’s and Ukraine’s constitutional law from the eighteenth to the twentieth century. Constitutional acts and international legal documents are analysed with the help of historical and comparative legal approaches. Knowledge of the historical experience of constitutional acts of European countries and Ukraine in the second half of the eighteenth to the twentieth century is necessary to create basic legal systems and protect human rights. Thus, the study employs historical-overlocal and comparative methods to explain Ukrainians’ responses to the European impact on their legal system. Issues of social and minority rights were gradually introduced into Ukrainian legislation, which proves the process of the country’s European integration due to the significant liberalisation of critical human rights values. The significance resides in recommendations on enhancing national legal tools to safeguard the rights of citizens effectively. The study’s practical significance lies in identifying critical stages in developing human rights and recommendations for improving national legal mechanisms to protect social and minority rights. The findings can be used to further enhance national legal systems in the context of European integration.